Digital Caricatures to Improve Anecdotal Writing Skills - Andy Syahputra Harahap; Siti Fatimah Zahra (International Journal of English and Applied Linguistics (IJEAL), 2023)
Caricature is a unique humor means of satire and criticism. This study aims to develop digital caricature media to learn anecdotal texts expressing social criticism through smiles. This study aims to describe the results of the needs analysis of students and classroom teachers. The research method uses the development steps of Alessi and Trollip. Learning media for writing anecdotal texts was developed based on the results of the analysis of the needs of students and teachers. The expert validation assessment consists of several aspects. These parts of material content, linguistic elements, and media aspects are carried out by two validations, namely material experts and media experts. The validity test of the material expert got a score of 33 with a percentage value of 92.5%, categorized as very feasible. The validity test of the media expert got a score of 45 with a percentage value of 93.75%, categorized as very feasible. The validity test of the linguist got a score of 13 with a percentage value of 81,25% classified as very feasible. Based on the results of expert validation, digital caricature media in revealing meaning through a developed smile can be very feasible for students in writing anecdotal texts.